If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x-5)=3(x+5)
We move all terms to the left:
-2(x-5)-(3(x+5))=0
We multiply parentheses
-2x-(3(x+5))+10=0
We calculate terms in parentheses: -(3(x+5)), so:We get rid of parentheses
3(x+5)
We multiply parentheses
3x+15
Back to the equation:
-(3x+15)
-2x-3x-15+10=0
We add all the numbers together, and all the variables
-5x-5=0
We move all terms containing x to the left, all other terms to the right
-5x=5
x=5/-5
x=-1
| 8x+0.6=48.6 | | M=0.15;b=2.25 | | (5x+10)/4=5(x+2) | | 3+1.5x+7=90-x | | 3x=-4x-20 | | 4(a-3)-6=6 | | 25=-2d+7 | | 26x+11=5(5x+2) | | 5x+10/4=5(x+2) | | (7t+2)-(-3t+1)=-3(-1-3t) | | X=-4x-20 | | M=-2;b=-11 | | 7+3x=5x-5 | | 5x+10/4=5(x2) | | y/5+7=2 | | 7x-37=47 | | 79.8=7(m+3.2) | | 3x+8=1-x-6 | | -6.4=8v | | −5(1−5x)+5(−8x−2)=−4x−8x | | 8x-26=62+6x | | (x-0.4)(3x-0.5)=0 | | y=1/2*(-6)+(-8) | | 3x-5(x-2)=-7+5x-39 | | 6x^2+91x+253=0 | | 5+2x=3x+10 | | y/8+17=7 | | 6=2=d | | 5x+7=3x-5 | | 8x-26=62=6x | | 3x-5(x-2)=7+5x-39 | | 21x-4-17x=2(2x-3)+2 |